Propylene glycol toxicity: a severe iatrogenic illness in ICU patients receiving IV benzodiazepines: a case series and prospective, observational pilot study - Wilson, Kevin C; Reardon, Christine; Theodore, Arthur C; Farber, Harrison W (Chest, 2005)
Benzodiazepines are commonly administered to medical ICU (MICU) patients. Propylene glycol (1,2-propanediol) is the solvent used to deliver lorazepam and diazepam IV. Although propylene glycol toxicity is increasingly recognized and reported, its incidence is unknown. Herein, we describe five MICU patients who acquired severe propylene glycol toxicity due to IV lorazepam or diazepam administration. Additionally, we evaluate the incidence of propylene glycol toxicity in MICU patients receiving IV lorazepam or diazepam. Case series and prospective, observational study. Eighteen-bed MICU in a 550-bed urban academic hospital. MICU patients administered IV benzodiazepines during a 3-month period were enrolled. Patients were categorized according to the IV benzodiazepine that they received. Laboratory data and highlights of their clinical course were recorded daily. The incidence of propylene glycol toxicity was determined and the groups compared. Forty-four patients were enrolled. Twenty-one patients received a benzodiazepine delivered in propylene glycol (lorazepam or diazepam), and 23 patients received a benzodiazepine delivered in an alternative solvent (midazolam). We found that four patients (19%) who received IV lorazepam or diazepam had metabolic evidence of propylene glycol toxicity. None of the patients had clinical deterioration. Neither metabolic abnormality nor clinical deterioration suggestive of propylene glycol toxicity were identified in subjects receiving IV midazolam. Propylene glycol toxicity is a potentially life-threatening iatrogenic complication that is common and preventable. It should be considered whenever a patient has an unexplained anion gap, unexplained metabolic acidosis, hyperosmolality, and/or clinical deterioration. Close monitoring of all patients receiving IV lorazepam or diazepam for early evidence of propylene glycol toxicity is warranted.